Bagaimana Pendidikan Demokrasi di Rumah Pintar Pemilu ? Peningkatan dan Pengawasan dalam Pemilu - Miftahur Rahmi; Alexsander Yandra; Dwi Herlinda; Harsini Harsini (JOELS: Journal of Election and Leadership, 2020)
This study discusses democracy and political education by the election smart house. The aim is to find out about Democracy and Political Education by the Election Smart House at the General Election Commission of Riau Province and the obstacles faced by the Election Smart House at the Riau Province General Election Commission in providing democratic and political education to voters. The data used are primary data with KPU officials and staff managing the Election Smart House. The secondary informants are staff of the Technical and Public Relations Sub-Division. Data collection techniques using observation techniques, interviews and documentation. The research method used is qualitative descriptive type and with a theoretical approach to the form of political education with indicators of formal political education, non-formal education and strengthened by the theory of political education dimensions with indicators of basic dimensions, objective dimensions, and institutional dimensions. The results of this study indicate that the role of the Election Smart House in the Riau Province General Election Commission in providing political education has not made a strong contribution and is even more passive, therefore the Election Smart House is still not widely known and the lack of budget so that they cannot freely in carrying out political education.